2021
DOI: 10.1155/2021/3631445
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Low Vegetable Consumption, Increased High-Sensitive C-Reactive Protein Level, and Cardiometabolic Risk in Korean Adults with Tae-Eumin: A Cross-Sectional Study

Abstract: An anti-inflammatory diet has many beneficial effects on cardiometabolic diseases. Constitution type of traditional Korean medicine can predict cardiometabolic risk factors. We examined the relationship between vegetable consumption and the high-sensitive C-reactive protein (hs-CRP) level on cardiometabolic risk factors in Korean adults by constitution types. Data from 1,983 eligible participants (mean age, 44.3 years) were included in the present cross-sectional study. The inflammatory status of the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 49 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…Participants' age, sex, BMI, health-related behaviors (smoking status, alcohol consumption, and physical activity level), working hours, KM type, and energy intake (kcal/day) were used as covariates in the statistical analysis. Previously, we confirmed high-risk associations with cardiometabolic outcomes (33) and inflammatory status (34) based on the two KM types in Korean adults. Age, BMI, and energy intake were used as continuous variables, and sex (male vs. female), smoking (no vs. yes), alcohol consumption (no vs. yes), physical activity (no vs. yes), working hours (≤8 h/day or ≤20 h/week vs. >8 h/day or >20 h/week), and KM type (Taeeum vs. Non-Taeeum) were used as categorical variables.…”
Section: Covariatessupporting
confidence: 63%
See 1 more Smart Citation
“…Participants' age, sex, BMI, health-related behaviors (smoking status, alcohol consumption, and physical activity level), working hours, KM type, and energy intake (kcal/day) were used as covariates in the statistical analysis. Previously, we confirmed high-risk associations with cardiometabolic outcomes (33) and inflammatory status (34) based on the two KM types in Korean adults. Age, BMI, and energy intake were used as continuous variables, and sex (male vs. female), smoking (no vs. yes), alcohol consumption (no vs. yes), physical activity (no vs. yes), working hours (≤8 h/day or ≤20 h/week vs. >8 h/day or >20 h/week), and KM type (Taeeum vs. Non-Taeeum) were used as categorical variables.…”
Section: Covariatessupporting
confidence: 63%
“…Consistently, elderly participants with CM patterns were more sedentary, more obese, had higher body fat mass, worsened cardiometabolic profiles, and high-risk sarcopenia or higher prevalence of SO than those without CM. Regarding the KM type, more participants in the CM group had Taeeum-type, with a predisposing metabolic risk (33,34) than those in the non-CM group. Our ongoing cohort study showed a higher prevalence of pre-metabolic diseases (MetS), lower nutritional status, higher high-sensitivity C-reactive protein (hs-CRP) level, and lower vegetable consumption in Taeeumtype middle-aged Korean adults (33,34).…”
Section: Lifestyle Risk Factors Of Sarcopenia Obesity Muscle Strength...mentioning
confidence: 97%
“…They serve as anti-inflammatory agents and antioxidants in the human body and regulate signaling pathways related to immune responses, resulting in reduced inflammation levels [ 9 , 10 , 11 , 12 ]. However, the effects of phytochemicals on inflammation may differ depending on ethnicity or food source type [ 12 , 13 , 14 , 15 , 16 , 17 ]. For example, a cross-sectional analysis of 5013 US men and women aged 30–75 years from the 1989–1990 Nurses’ Health Study and the 1993–1995 Health Professionals Follow-Up Study showed that nut consumption was inversely associated with hs-CRP levels [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of prior epidemiological studies that have investigated the association between phytochemicals and hs-CRP have been conducted in western countries and focused on a single food item or compound. Limited data is available in the Asian population, including Koreans [ 14 ], especially for comprehensively evaluated health effects of dietary phytochemicals in large epidemiologic study designs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it seems that obesity contributes to the formation of a pro-inflammatory environment [ 62 ]. In addition, several studies recommend that a diet rich in vegetables, fruits, whole grains and nuts has a beneficial effect on reducing CRP levels [ 64 , 65 ].…”
Section: Biomarkers With Increased Concentration In Sarcopeniamentioning
confidence: 99%